Exorcising “Racecraft”: Toward the RaceSyllabus - Asare, Abena Ampofoa (Radical Teacher, 2018)
This paper, based on my experiences teaching Africana Studies at a Northeastern public university, argues that anti-racist pedagogy must include a RaceSyllabus which reveals to diverse students the artificiality of race as a man-made ideology, neither biologically rooted nor divinely-inspired. Barbara Jean Fields and Karen Fields use the term racecraft to describe how race ideology persists as a subterranean, almost occult force in American institutions and minds. In my teaching I have developed a syllabus which propels students into a novel mental terrain where the racial categories we inherit and inhabit are neither inevitable or natural, but instead are created and re-created by our national economic, political, social, and cultural choices. The RaceSyllabus includes two interrelated learning objectives which, together, propel students to see outside our society’s race-tinted lenses. 1. Students should consider that racial identities in the United States are historically specific. 2. Students should consider that racial identities are geographically specific. These two insights, when taught together, are remarkably effective in exposing the artificiality of our national racial myths.